Financial market reaction to R&D volatility in the pharmaceutical industry. A multi-country study - Mironiuc, Marilena; Huian, Maria Carmen; Țaran, Alina; Curea, Mihaela (Journal of Business Economics and Management, 2022)
Corporate management is often accused of short-term oriented behaviour related to R&D expenditures. This study analyses the influence of R&D volatility and R&D intensity on the market capitalization of pharmaceutical and medical research companies from Europe, considering the institutional context and several firm characteristics. Panel regression estimations on a sample of 217 companies for 2014–2019 indicate that R&D volatility adversely affects market value. The analysis is conducted on the entire sample and on sub-samples determined based on the positive and negative values of the R&D volatility. This differentiates between the continuous and the disrupting effect of R&D activities and the firm’s shift between exploratory and exploitative innovations. The positive volatility sub-sample provides consistent evidence of a significant negative influence of the R&D volatility on the market value. For the negative volatility sub-sample, R&D intensity and its interaction with R&D volatility have a significant positive effect, consistent over the alternative estimations. We conclude that the market influence of the R&D expenditure is related to the sign of volatility and depends on the proportion of R&D expenditure, especially when the volatility is negative. Our findings provide valuable insights for managers, investors, analysts, and other stakeholders about the market reaction to R&D volatility.